2021
DOI: 10.3389/fphar.2021.759172
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol Inhibits MDSCs and Promotes M1 Macrophages in Mice With Orthotopic Pancreatic Tumor

Abstract: The poor immunotherapy of pancreatic cancer is mainly due to its complex immunosuppressive microenvironment. The Mediterranean diet contributes to low cancer incidence. Hydroxytyrosol (HT) derived from olive oil has multiple health-promoting effects, but its therapeutic effect on pancreatic cancer remains controversial. Here, we evaluated the inhibitory effect of HT on mouse pancreatic cancer, and the effect of HT on the immune microenvironment. We found that HT can inhibit the proliferation of Panc 02 cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…[ 51 ] The proposed drug delivery system could effectively optimize the distribution of the inhibitor, which is the premise of successful immunotherapy, since p ‐STAT3 is the key pivot in modulating the immunosuppression microenvironment in pancreatic cancer therapy. [ 52 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 51 ] The proposed drug delivery system could effectively optimize the distribution of the inhibitor, which is the premise of successful immunotherapy, since p ‐STAT3 is the key pivot in modulating the immunosuppression microenvironment in pancreatic cancer therapy. [ 52 ]…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the compound inhibited the proliferation of tumour cells, was able to activate the signal transducers and activators of the transcription 3 (STAT 3)/CCND1 signalling pathway, increased the proportion of M1 macrophages, and enhanced the anti-cancer effects of the anti-CD 47 antibody. Additionally, the combination of HT with plumbagin (PLB) resulted in more cell death compared with HT or PLB alone [ 96 ].…”
Section: Potential Effects Of Oleuropein and Hydroxytyrosol On Neurob...mentioning
confidence: 99%
“…In an in vivo orthotopic model of pancreatic cancer, obtained by injecting mouse pancreatic cancer cells Panc02 in C57BL/6 mice, proved that 200 mg/kg HT for 10 days suppressed tumor growth and proliferation. These results seem to depend on the modulation of the tumor microenvironment, since HT was able to reduce the accumulation of myeloid-derived suppressor cells in lymphoid organs, bone marrow, and tumor tissues [ 81 ].…”
Section: Effects Of Ole and Ht On Solid Tumorsmentioning
confidence: 99%
“…Treatment of mouse pancreatic cancer cell line Panc02 with 50 μM, 150 μM, and 200 μM HT for 48 h elicited a dose-dependent inhibition of cell proliferation and induction of apoptosis. Further experimental evidence revealed that 100 μM HT inhibited the expression of phospho-STAT3 and Cyclin D1 after 24 h [ 81 ].…”
Section: Effects Of Ole and Ht On Solid Tumorsmentioning
confidence: 99%